Side-slipping of a radiating particle - Artru, X.; Bignon, G.; Qasmi, T. (Вопросы атомной науки и техники, 2001)
Radiation reaction is revisited, first in a new classical approach, where the physical particle 4-momentum is redefined as the energy-momentum flux across the future light cone and is not parallel to the 4-velocity. Then in a semi-classical approach, it is shown that, when emitting a photon, the particle "side-slips" transversally to its initial momentum, justifying the non-collinearity between momentum and mean velocity. Side-slipping is finally checked in a pure quantum mechanical treatment of synchrotron radiation.